Adaptation of the international physical activity questionarie for the elderly Adaptação do questionário internacional de atividade física para idosos - Mazo G.Z.* (2010)
The International Physical Activity Questionnaire (IPAQ) estimates the weekly energy expenditure for physical activities (PA). This instrument was validated for use with Brazilian older adults. The need to adapt the structure and application of the IPAQ arose from the difficulties of older adults to correctly measure the number of days, time and intensity of PA (domains) during a normal week and the difficulties encountered by the interviewers in field research. The adapted IPAQ consists of five domains and 15 questions and is applied by interview because of the low educational level of Brazilian older adults. The instrument is applied in its long form to permit better discrimination of PA in each domain and refers to a normal week to help recall morning, afternoon and evening activities. In addition, it includes details about mild, moderate and vigorous intensity. The training of the interviewers is fundamental. The report of the IPAQ adapted for older adults should be delivered in minutes per week and should use the classification active (≤ 150 min/week). The IPAQ adapted for older adults is an international instrument that is valid for the Brazilian elderly population. The instrument is a noninvasive easily applied method of low cost that reaches large population groups, among other advantages.